Antifungal activity of endophytic Streptomyces strains from Dendrobium orchids and the secondary metabolites of strain DR7-3 with its genome analysis - Nisachon Tedsree, Kittisak Likhitwitayawuid, Boonchoo Sritularak, Karaked Tedsree, Somboon Tanasupawat (Journal of Applied Pharmaceutical Science, 2022)
Chemical fungicides are widely used in the agriculture sector and cause severe environmental problems. Biological control, a method using antagonistic organisms, has been considered one of the most promising strategies to tackle this issue. Actinomycetes, particularly Streptomyces strains, produced diverse classes of bioactive secondary metabolites. In this study, four Streptomyces strains, DR5-1, DR7-3, DR8-5, and DR8-8, isolated from three Dendrobium species (Orchidaceae), exhibited significant antifungal activity against five phytopathogenic fungi, particularly with high potency against Curvularia oryzae. The bacterial identification was performed based on phenotypic and chemotaxonomic characteristics, including the 16S rRNA gene sequence. Strain DR7-3 from the roots of Dendrobium findlayanum exhibited high antifungal activity, and its culture filtrate caused damage to the cell structure of C. oryzae SA04. It was identified as Streptomyces solisilvae based on the average nucleotide identity, ANIb (98.49%), and DNA–DNA hybridization value (88.40%). The EtOAc extract from strain DR7-3 was analyzed by the gas chromatography-mass spectrometry method. Among the 15 identified compounds, eicosane, phenol-2,4-bis(1,1- dimethylethyl), hexadecane, and hexadecanoic acid-methyl ester showed significant antifungal activity. The draft genome sequence analysis of strain DR7-3 revealed 72 putative biosynthetic gene clusters of secondary metabolites. The genome alignment indicated that 13 gene clusters are involved in the biosynthesis of these antifungal metabolites. These results suggested that strain DR7-3 could be a promising candidate for developing new and safe microbial biological control agents for application in agricultural fields.
Keywords: Antifungal activity, Dendrobium, GC-MS, genome analysis, secondary metabolites, orchids, Streptomyces